Design of experimental food patches to measure foraging intensity for octopus: a case study with the giant Pacific octopus Enteroctopus dofleini. (31st December 2020) - Chancellor, Stephanie; Scheel, David; Brown, Joel S
ABSTRACT: In a study of the foraging behaviour of the giant Pacific octopus Enteroctopus dofleini, we designed two types of experimental food patches to measure habitat preferences and perceptions of predation risk. The first patch successfully measured giving-up densities (GUDs), confirmed by octopus prey presence and higher foraging at sites with historically greater octopus presence. However, nontarget foragers also foraged on these experimental food patches. Our second floating patch design successfully excluded nontarget species from subtidal patches, and from intertidal patches at high tide, but allowed for foraging by E. dofleini . The second design successfully measured GUDs and suggested that octopus preferred foraging in a subtidal habitat compared to an intertidal habitat. We ascribe the higher GUD in the intertidal habitat to its higher predation risk relative to the subtidal habitat. The second patch design seems well suited for E. dofleini and, in conjunction with a camera system, could be used to provide behavioural indicators of the octopus's abundance, perceptions of habitat quality and predation risk.